HgCdTe quantum wells grown by molecular beam epitaxy - Dvoretsky, S.A; Ikusov, D.G.; Kvon, Z.D.; Mikhailov, N.N.; Remesnik, V.G.; Smirnov, R.N.; Sidorov, Yu.G.; Shvets, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
CdxHg₁₋xTe-based (x = 0 – 0.25) quantum wells (QWs) of 8 – 22 nm in
thickness were grown on (013) CdTe/ZnTe/GaAs substrates by molecular beam epitaxy.
The composition and thickness (d) of wide-gap layers (spacers) were x ∼ 0.7 mol.frac.
and d ∼ 35 nm, respectively, at both sides of the quantum well. The thickness and
composition of epilayers during the growth were controlled by ellipsometry in situ. It
was shown that the accuracy of thickness and composition were ∆x = ± 0.002, ∆d =
± 0.5 nm. The central part of spacers (10 nm thick) was doped by indium up to a carrier
concentration of ∼10¹⁵ cm⁻³
. A CdTe cap layer 40 nm in thickness was grown to protect
QW. The compositions of the spacer and QWs were determined by measuring the Е₁ and
Е₁+∆₁ peaks in reflection spectra using layer-by-layer chemical etching. The galvanomagnetic
investigations (the range of magnetic fields was 0 – 13 T) of the grown QW
showed the presence of a 2D electron gas in all the samples. The 2D electron mobility
µe = (2.4 – 3.5)×10⁵
cm²
/(V·s) for the concentrations N = (1.5 – 3)×10¹¹ cm⁻² (x < 0.11)
that confirms a high quality of the grown QWs.